Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Luật Nhà ở (sửa đổi) (Kèm Báo cáo tóm tắt) - Ủy ban Thường vụ Quốc hội (2023)
Toàn văn Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Luật Nhà ở (sửa đổi) (Kèm Báo cáo tóm tắt).